DAMPAK PEMUTUSAN HUBUNGAN KERJA TERHADAP PERENCANAAN DAN PENGEMBANGAN KARIR - Mardiyah; Nabila, Farah Diva; Adawiyah, Alfina Robiatul; Efendi, Ahmad Faishol; Asy’ari, Ach. Baidlowi (Cahaya Ilmu Bangsa, 2024)
This article discusses the impact of layoffs on individual career planning and development. Layoffs not only affect economic stability, but also have significant impacts on one's mental health, self-esteem, and professional identity. This article uses a library research method. Based on library research, layoffs can cause severe psychological stress, trigger feelings of career loss, and reduce self-confidence. The impact varies, depending on the individual's ability to adapt and the social support they have. Although the impact of layoffs is very negative, there is also the potential to use it as an opportunity to explore new career paths, develop skills, or start a new business. This article highlights the importance of social support, retraining, and developing adaptive thinking patterns in dealing with changes caused by layoffs. Keywords: Impact, Layoffs, Career